Probing the physical limits of reliable DNA data retrieval - Lee Organick (Nature Portfolio, 2020)
The physical limits and reliability of PCR-based random access of DNA encoded data is unknown. Here the authors demonstrate reliable file recovery from as few as ten copies per sequence, providing a data density limit of 17 exabytes per gram.